A review on the toxic E-waste killing health and environment – Today's global scenario. (2021) - Beula, D.; Sureshkumar, M.
Abstract: Electronic waste or e-waste is one of the fastest growing problems globally. E-waste comprises of many number of components, that includes toxic substances too which can cause an intense impact on human health and the environment if not handled properly. Waste electrical and electronic equipment (WEEE) is becoming serious threat to the whole world. Toxic substances present in the e-waste when mixed in air and soil, leads to harmful effects to the environment either directly or in directly. There is an evidence that when the groundwater and soil gets contaminated due to e-waste, may cause harmful effects in some agricultural or manufactured products. Risk assessments has predicted that, Lead (Pb) and Copper (Cu) originating/extracted from circuit boards during recycling process have the potential to pose serious health risks to the workers and local residents of Guiyu, especially children who involves in this process. Series health issues were faced by the peoples in Guiyu, due to the consequences of uncontrolled e-waste recycling, and it has been reported as a specimen study to other countries. This review focuses on stating the serious issues on e-waste, and its impact on humans' health, environment, and soil globally. Further, the current progress on e-waste management and serious care needed to protect the soil and environment worldwide for the next generation is strongly registered.